Association of mean platelet volume with risk of venous thromboembolism and mortality in patients with cancer - Riedl, Julia; Kaider, Alexandra; Reitter, Eva-Maria; Marosi, Christine; Jäger, Ulrich; Schwarzinger, Ilse; Zielinski, Christoph; Pabinger, Ingrid; Ay, Cihan (Thrombosis and Haemostasis, 2014)
Venous thromboembolism (VTE) is a frequent complication in cancer patients. Mean platelet volume (MPV) has been associated with arterial and venous thrombosis in patients without cancer. We analysed MPV in cancer patients and investigated the association of MPV with risk of VTE and mortality. MPV was routinely determined in the Vienna Cancer and Thrombosis Study, a prospective, observational cohort study of patients with newly diagnosed or progressive cancer after remission. Study endpoints were occurrence of symptomatic VTE or death during a maximum follow-up of two years. Out of 1,544 included patients, 114 (7.4%) developed VTE and 573 (37.1%) died during a median observation time of 576 days. High MPV ≥75th percentile of the study population; ≥10.8 fL) was associated with decreased risk of VTE compared to MPV below the 75th percentile (HR [95% CI]: 0.59 [0.37–0.95], p=0.031). In multivariable analysis, including age, sex, cancer groups, newly diagnosed vs recurrent disease, platelet count and soluble P-selectin, this association remained statistically significant (0.65 [0.37–0.98], p=0.041). Mortality of patients with MPV (≥75th percentile was significantly decreased compared to those with lower MPV (0.72 [0.59–0.88], p=0.001). Two-year probability of VTE and overall survival was 5.5% and 64.7% in patients with high MPV compared to 9% and 55.7% in those with lower MPV. In conclusion, high MPV is associated with decreased VTE risk and improved survival in cancer patients. This finding is contrary to results observed in patients without cancer. Further studies are needed to confirm our results and elucidate underlying mechanisms.Previous presentations of this manuscript: Data from this study were presented in part at the Annual Spring Meeting of the Austrian Society for Haematology and Oncology (OeGHO) in Linz, Austria, and as an oral presentation at the XXIV. Congress of the International Society on Thrombosis and Haemostasis (ISTH) 2013 in Amsterdam, the Netherlands.
Keywords: Mean platelet volume; cancer; venous thromboembolism; platelets; mortality